Investigating Dual Character of Atmospheric Ammonia on Particulate NH4NO3: Reducing Evaporation Versus Promoting Formation - Hongxiao Huo; Yating Gao; Lei Sun; Yang Gao; Huiwang Gao; Xiaohong Yao (Atmosphere)
Ammonium nitrate (NH4NO3) is a major constituent of fine particulate matter (PM2.5), playing a critical role in air quality and atmospheric chemistry. However, the dual regulatory role of ammonia (NH3) in both the formation and volatilization of NH4NO3 under ambient atmospheric conditions remains inadequately understood. To address this gap, we conducted high-resolution field measurements at a clean tropical coastal site in China using an integrated system of Aerosol Ion Monitor-Ion Chromatography, a Scanning Mobility Particle Sizer, and online OC/EC analyzers. These observations were complemented by thermodynamic modeling (E-AIM) and source apportionment via a Positive Matrix Factorization (PMF) model. The E-AIM simulations revealed persistent thermodynamic disequilibrium, with particulate NO3− tending to volatilize even under NH3gas-rich conditions during the northeast monsoon. This suggests that NH4NO3 in PM2.5 forms rapidly within fresh combustion plumes and/or those modified by non-precipitation clouds and then undergoes substantial evaporation as it disperses through the atmosphere. Under the southeast monsoon conditions, reactions constrained by sea salt aerosols became dominant, promoting the formation of particulate NO3− while suppressing NH4NO3 formation despite ongoing plume influence. In scenarios of regional accumulation, elevated NH3 concentrations suppressed NH4NO3 volatilization, thereby enhancing the stability of particulate NO3− in PM2.5. PMF analysis identified five source factors, with NO3− in PM2.5 primarily associated with emissions from local power plants and the large-scale regional background, showing marked seasonal variability. These findings highlight the complex and dynamic interplay between the formation and evaporation of NH4NO3 in NH3gas-rich coastal atmospheres.